Correction: A quantitative analysis of Final Palaeolithic/earliest Mesolithic cultural taxonomy and evolution in Europe. - Felix Riede; David N Matzig; Miguel Biard; Philippe Crombé; Javier Fernández-Lopéz de Pablo; Federica Fontana; Daniel Groß; Thomas Hess; Mathieu Langlais; Ludovic Mevel; William Mills; Martin Moník; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0299512.].